Analyzing the effectiveness of waiting times at the pharmacy of the King Hamad University Hospital - Al-Mofleh, Anwar; Alseddiqi, Mohamed; Najam, Osama; AlMannaei, Budoor; Albalooshi, Leena (IAES International Journal of Robotics and Automation (IJRA), 2025)
This study investigates the efficiency of waiting times at the pharmacy of King Hamad University Hospital, with a primary focus on optimizing patient experiences. Efficient pharmacy services are vital for ensuring the timely provision of medications to patients. Prolonged waiting times not only affect patient satisfaction but may also have implications for overall healthcare outcomes. To assess the effectiveness of waiting times, we conducted comprehensive analysis, including data collection, surveys, and observations. Our findings reveal valuable insights into the current state of pharmacy operations and the patient experience. We explore factors contributing to waiting times, such as prescription processing, queue management, and staff allocation. Through this analysis, we aim to provide actionable recommendations to enhance pharmacy efficiency, reduce waiting times, and improve patient satisfaction. Our study underscores the importance of optimizing pharmacy operations to ensure that patients receive timely and high-quality healthcare services. By addressing these issues, King Hamad University Hospital can not only enhance the overall patient experience but also contribute to better healthcare outcomes and increased operational efficiency. This research serves as a valuable resource for healthcare administrators, policymakers, and practitioners seeking to improve pharmacy services and patient satisfaction in hospital settings.